Leadership, work environment, and work motivation on employee performance at PT Telkomsel’s IT directorate - Primanda, Galih; Nurhayati, Popong; Sukmawati, Anggraini (Indonesian Journal of Multidisciplinary Science, 2024)
PT Telkomsel acquired Fixed Line Business from Telkom Indonesia on July 1st, 2023, integrating IndiHome services. The acquisition process involved system integration and employee joining. A research study was conducted to examine the impact of leadership, work environment, and motivation on employee performance at the IT Directorate of PT Telkomsel. Data was collected through questionnaires distributed via Google Form and analyzed using Likert scale and structural equation model partial least square. Results showed that leadership factors positively influence employee performance, while the merger of IndiHome business line did not affect IT director performance. Leaders' ability to encourage creativity, skill development, and collaboration were the most influential management indicators. Working environment factors, such as harmonious relationships between managers and employees, also positively impacted employee performance. Work facilities were crucial in supporting employee productivity. Motivation also positively influenced employee performance.